Functional transposition of renal functions to the posterior intestine during maturation in male three-spined stickleback - Yared H Bezabhe; Berkay Paylar; Asmerom Seyoum; Bertil Borg; Per-Erik Olsson (Scientific Reports)
Abstract During the breeding season, the male stickleback proximal tubule of the kidney undergoes hypertrophy. This is due to the synthesis of the nest building protein spiggin, in response to increased levels of 11-ketotestosterone. The increased protein synthesis that is initiated during breeding alters the kidney function and the ability to secrete excess water, to osmoregulate, in fresh water. It has earlier been shown that there exist organ specific differences in transport proteins between mature and non-mature three-spined stickleback. To understand the molecular mechanisms compensating for kidney functions, this study examined transport genes responsible for functional changes between the kidney and intestine. RNA sequencing was performed on castrated and 11-ketoandrostenedione (11KA)-treated male stickleback. Results showed organ-specific responses: 2,549 differentially expressed genes (DEGs) in the kidney and 885 in the posterior intestine, with 210 shared between the organs. Solute transporters, aquaporin 10a and cadherin-17, were upregulated in the posterior intestine but downregulated in the kidney in 11KA treated males. Enrichment analysis revealed distinct biological processes, primarily involving solute transporters, indicating functional adaptation. While amino acid and ion transport were downregulated in the kidney, compensatory transport was observed in the posterior intestine. However, cellular hexose transporters were downregulated in both organs, suggesting a reduction in glucose absorption and passive water diffusion. The present study shows that androgens alter the expression of cellular transporters and redirect functions of the kidney to the posterior intestine. The results also indicate reduced glucose absorption in breeding, male three-spined stickleback.